EXPANDING THE UNDERSTANDING OF HEALTH AS AN INTANTGIBLE GOOD TODAY - Mazure, Līga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
In classical interpretation, health is defined as a subjective right to this intangible good, which is only characteristic of humans. However, it could be evaluated whether health as a relevant interest can be characteristic of any other subject, expanding the existing understanding of health. The modern legal system distinguishes between subjects with different levels of protection of their interests, i.e., the subjects of rights and the subjects of interests. And a trend is observed where health is also recognised as a category characteristic of the subjects of interests, adjusting the former understanding of the concept of health. Thus, by expanding the understanding of health, types of health can be distinguished according to the subject of interests, e.g., health of a legal person, health of a conceived person, etc., adapting the understanding of health to the criteria of the subject of interests. The research aim is to analyse the expansion of the understanding of health and suggest a division of the types of health in accordance with the modern legal system. The following primary research methods were used in the study: analytical, systemic, teleological.